Analisis Perhitungan Struktur Bangunan Rumah Toko (Ruko) Jalan Terminal Kota Pagar Alam - Sumarsono Sumarsono; Melinda Sri Wahyuni (LPPM Sekolah Tinggi Teknologi Pagar Alam, 2016)
The frame building system consists of horizontal elements (beams), vertical (columns) and floor plates. The selection of structural materials to used for certain buildings is influenced by the height and span of the structure, availability of materials in the market and foundation conditions. In the supply of this material, not all imported first, but must be planned according to the needs and must also be adjusted to the time of use so that the quality or quality of the material can meet the desired target. The good quality materials and work must follow Normalization in Indonesia, standard construction industry and national regulations. The purpose of this study is find out how big the dimensions of the structure are able to withstand the load acting on the main structure in the construction of the Shop and House. Plates of roof and floor plates with a span of 5 meters are planned to be 12 cm thick or 0.12 meters using reinforced steel D10-100 (with As area = 785.4 mm2). The roof beam with a span of 5 m is used to measure the beam size 15 cm x 30 cm, used reinforcement steel 6D14 (As = 923.16 mm2) with reinforcement D-6 (Av = 28.26 mm2) for stirrups with a maximum spacing of 135 mm for overall beam length. Floor beams with a span of 5 m are used for beam dimensions measuring 20 cm x 33 cm, using reinforced steel 8D14 (with As area = 1230.88 mm2) with D-8 reinforcement (Av = 50 mm2) for stirrups with a maximum spacing of 180 mm for the overall length of the beam. Columns with a height of 4 m are used for column dimensions measuring 210 mm x 210 mm, using reinforcement steel 8D14 (1230.88 mm2).